Organizational climate and employee satisfaction following the reform of social services - Babšek, Matej (Dynamic relationships management journal, 2024)
The main goal of the paper is to present how employees of social services in Slovenia view the reorganization carried out in 2018 with the purpose to draw attention to the importance of both the organizational climate and employee satisfaction before and after the reorganization given the established connection between these constructs. In the research, mixed methods were used, specifically an explanatory sequential design. In the quantitative phase, an online survey adapted to these organizations was conducted among employees, while in the following qualitative phase in-depth semi-structured interviews were performed with managers and professional workers. The results show the failure of the reorganization of social services because the set objectives were not accomplished. Employees rated both organizational climate and employee satisfaction worse after the reorganization than before it. Here, the most critical aspects are the lack of knowledge concerning the new organization’s mission, vision, and goals, coupled with the employees’ lack of identification with them. While, as expected, a connection exists between climate and satisfaction as well as satisfaction and attitudes to the reorganization, the research also reveals the important connection between digitalization and the principles of good governance pursued by these services. The findings of the research may be valuable for policymakers and practitioners while designing and implementing future reforms in social services organizations in terms of ensuring a favorable work climate and employee satisfaction.
Keywords: employee satisfaction; organizacijska klima; organizational climate; reform; reforma; reorganizacija; reorganization; Slovenia; Slovenija; social services; socialne storitve; zadovoljstvo zaposlenih